2013
DOI: 10.1029/2012jd018327
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbons in the upper troposphere and lower stratosphere observed from ACE‐FTS and comparisons with WACCM

Abstract: [1] Satellite measurements from the Atmospheric Chemistry Experiment Fourier Transform Spectrometer (ACE-FTS) are used to examine the global, seasonal variations of several hydrocarbons, including carbon monoxide (CO), ethane (C 2 H 6 ), acetylene (C 2 H 2 ), and hydrogen cyanide (HCN). We focus on quantifying large-scale seasonal behavior from the middle troposphere to the stratosphere, particularly in the tropics, and furthermore make detailed comparisons with the Whole Atmosphere Community Climate Model (WA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
57
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 132 publications
3
57
0
Order By: Relevance
“…Randel et al (2007) proposed that this behavior results primarily from vertical transport; seasonal variations in the Brewer-Dobson circulation acting on the strong background vertical gradient in ozone can account for the phase, amplitude and vertical structure of the ozone annual cycle. Similar effects occur for other tracers with strong vertical gradients across the tropopause, including carbon monoxide (CO) or tropospheric hydrocarbons such as ethane (C 2 H 6 ) (Park et al, 2013). On the other hand, complementary modeling analyses using a Lagrangian transport framework suggest that the large annual cycle in ozone mainly results from horizontal in-mixing, in particular due to transport associated with the Asian summer monsoon anticyclone (Konopka et al, 2009(Konopka et al, , 2010.…”
Section: Introductionmentioning
confidence: 92%
“…Randel et al (2007) proposed that this behavior results primarily from vertical transport; seasonal variations in the Brewer-Dobson circulation acting on the strong background vertical gradient in ozone can account for the phase, amplitude and vertical structure of the ozone annual cycle. Similar effects occur for other tracers with strong vertical gradients across the tropopause, including carbon monoxide (CO) or tropospheric hydrocarbons such as ethane (C 2 H 6 ) (Park et al, 2013). On the other hand, complementary modeling analyses using a Lagrangian transport framework suggest that the large annual cycle in ozone mainly results from horizontal in-mixing, in particular due to transport associated with the Asian summer monsoon anticyclone (Konopka et al, 2009(Konopka et al, , 2010.…”
Section: Introductionmentioning
confidence: 92%
“…In contrast to MIPAS observations, in this region the ACE-FTS distribution is dominated by measurements from January, when the plume is already considerably weaker than in December. HCN climatologies derived from ACE-FTS measurements have already been published by Lupu et al (2009), Randel et al (2010 and Park et al (2013). As a more quantitative intercomparison, Fig.…”
Section: Comparison With Ace-fts and With Intex-b Measurementsmentioning
confidence: 99%
“…However, they expected an irregular cycle for a longer time series, because Indonesian biomass burning is strongly influenced by El Niño events. Park et al (2013), who analysed a longer time series of tropical HCN from ACE-FTS, found tape recorder cycles of 1 and 2 years. Thus the question of whether there is a periodicity in the HCN tape recorder signal is still open, and the long time series of MIPAS (Michelson Interferometer for Passive Atmospheric Sounding) data is well suited for providing insight into this problem.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown previously, the ACE-FTS measures VMR profiles of CO (Clerbaux et al, 2008), hydrocarbons, such as HCN, C 2 H 6 , C 2 H 2 (Park et al, 2013) and HCOOH (González Abad et al, 2009) in the upper troposphere and lower stratosphere. In addition to these species, CH 3 OH and H 2 CO have been measured by the ACE-FTS globally (Dufour et al, , 2009) and in biomass burning plumes over northern high latitudes Tereszchuk et al, 2011Tereszchuk et al, , 2013 and in the Southern Hemisphere .…”
Section: Ace-fts Measurementsmentioning
confidence: 99%